Effect of breastfeeding duration on lung function, respiratory symptoms and allergic diseases in school‐age children. Issue 6 (17th March 2020) - Gorlanova, Olga; Appenzeller, Rhea; Mahmoud, Yasmin S.; Ramsey, Kathryn A.; Usemann, Jakob; Decrue, Fabienne; Kuehni, Claudia E.; Röösli, Martin; Latzin, Philipp; Fuchs, Oliver; Soti, Andras; Frey, Urs; et al.
Abstract: Background: A positive effect of breastfeeding on lung function has been demonstrated in cohorts of children with asthma or risk for asthma. We assessed the impact of breastfeeding on lung function and symptoms at the age of 6 years in an unselected, healthy birth cohort. Methods: We prospectively studied healthy term infants from the Bern‐Basel Infant Lung Development (BILD) cohort from birth up to 6 years. Any breastfeeding was assessed by weekly phone calls during the first year of life. Risk factors (eg, smoking exposure, parental history of allergic conditions, and education) were obtained using standardized questionnaires. The primary outcomes were lung function parameters measured at 6 years of age by spirometry forced expiratory volume in 1 second, body plethysmography (functional residual capacity [FRCpleth ], the total lung capacity [TLCpleth ], and the effective respiratory airway resistance [Reff ]) and fractional exhaled nitric oxide (FeNO). Secondary outcomes included ever wheeze (between birth and 6 years), wheeze in the past 12 months, asthma, presence of allergic conditions, atopic dermatitis, rhinitis, and positive skin prick test at the age of 6 years. Results: In 377 children the mean breastfeeding duration was 36 weeks (SD 14.4). We found no association of breastfeeding duration with obstructive or restrictive lung function and FeNO. After adjustment for confounders, we found no associations of breastfeeding duration with respiratory symptoms or the presence of allergic conditions. Conclusion: This study found no evidence of an association between breastfeeding and comprehensive lung function in unselected healthy children with long‐term breastfeeding. Our findings do not support the hypothesis that the duration of breastfeeding has a direct impact on lung function in a healthy population with low asthmatic risk.